Použití scruberů při čištění vzduchu - Krištof, Ondřej (Vysoké učení technické v Brně. Fakulta chemická, 2012)
Diplomová práce je zaměřena na problematiku separace plynných polutantů ze znečištěných směsí plynů do kapaliny pomocí absorpčního zařízení. Teoretická část se zabývá především popisem absorpčního procesu, způsobu vyjadřování a faktorů ovlivňujících rychlost přestupu kontaminantů mezi fázemi. Experimentální část se zabývá závislostí přestupu oxidu uhličitého obsaženého ve vzdušné směsi do vodného roztoku hydroxidu sodného na procesních podmínkách separace poloprovozní pračky vzduchu.

The Diploma thesis is focused on the separation of gaseous pollutants from contaminated mixtures of gases into liquids using absorbent device. The theoretical part is mainly concerned with describing the absorption process, the method expression and the factors influencing the rate of transfer of contaminants between phases. The experimental part deals with the dependence of transfer of carbon dioxide contained in an air mixture into an aqueous solution of sodium hydroxide on the process conditions of separation in pilot scrubber.
Air contaminants separation process
Keywords: absorpce; kontaminace vzduchu; separace plynných kontaminantů; separace plynných oxidů; separace par; absorption; air pollution; separation of gaseous pollutants; separation of gaseous oxides; vapour separation